The Spatial Learning Task of Lhermitte and Signoret (1972): Normative Data in Adults Aged 18–45 - Collins, Alana; Saling, Michael M.; Wilson, Sarah J.; Jackson, Graeme D.; Tailby, Chris (Frontiers in Psychology, 2022)
Objective: The Spatial Learning Task of Lhermitte and Signoret (1972) is an object-location arbitrary associative learning task. The task was originally developed to evaluate adults with severe amnesia. It is currently used in populations where the memory system either is not yet fully developed or where it has been compromised (e.g. epilepsy, traumatic brain injury, electroconvulsive therapy, cerebrovascular disease, dementia). Normative data have been published for paediatric cohorts and for older adults, however no data exist for the intervening adult years. Method: Here we address this gap, collecting normative data from 101 adults aged 18-45. Results: Our data indicate that performance on the Spatial Learning Task is not influenced by age, gender, level of education or overall IQ. Less than 10% of the variance in learning scores is associated with variability in verbal memory. Ninety percent of participants achieved perfect scores on two successive trials (T2Cr) within five or fewer trials on the Spatial Learning Task. A T2Cr score of 6 is suggestive of impairment and a T2Cr score of 7 or more is statistically abnormal. Conclusions: These data expand the clinical utility of the Spatial Learning Task in the adult population. Future work should examine performance in lower IQ cohorts, including intellectual disability, and explore sensitivity to disease factors such as laterality of mesial temporal lobe damage.